Diet of Inflammatory Bowel Disease Patients, in Gastrointestinal and Liver Center, Baghdad, 2020 - Mohsin Ahmed Aldelf; Nawal M Alkhalidi; Saif M Bader; Zainab Gh Wafi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Iinflammatory bowel disease (IBD) comprises a group of chronic immune disorders of unknownetiology characterized by intestinal inflammation which subsequently leads to debilitating symptoms whichcan adversely affect performance and quality of life. Crohn’s disease (CD) and ulcerative colitis (UC) arethe two most common phenotypes.Patients and method: The cross-sectional study with the diagnosis of either Crohn’s disease or ulcerativecolitis. The data collection was carried out from 25 september to 10 november 2020. From gastroinestinaltract and liver center ,Baghdad . Convienant sample are willing to participate. By questionnaire.Bodyweight and hieght was measured. Body mass index (BMI) was calculated . Recorded intake of all food anddrinks during last 24 hours. By Excil caculation program , the enegy intake of one day was calculated bymifflin-St.jeor method .The my pyramid plan for daily food and calories intake as recommended pattrern. Statitcal analysis were performed using SPSS 23 . Data described as mean±standerd deviation (SD).Datawere checked for normal distribution using t -test or chi square .The level of significance in the study wasp < 0.05 .Result: All the participants (55;100%) were low milk group servings intake( P<0.001), also( 74.5% ) ofparticipants were low fruit group servings intake (P<0.001) ,(92.7% ) 0f participants was low vegetablesgroup servings intake (P<0.001) , but ( 87.3% )Of participants were high grain group servings intake(P<0.001) ,( 65.5% ) of participaints was low protein group servings (P=0.041) , the fat group servingintake is low among (90.9%) of participants (P<0.001) , 52.7% of participants low energy intake. The meanBMI for both genders was in the normal range (23.16 ± 5.33) as (49.1%) of participants , only 14.5 % wasunderweight , 29.1% was overweight and 7.3% was obese. The participants live in aurban area as (89.1%) .The ocupation of them were 25% housewife,student (23.6%),employers (16.4%) and the rest with differentoccupations. The education of participants were primary school (36.4%) ,intermediate school(12.7%) ,secondry school were (14.5%), graduated were (12.7%) and the rest in the different educations. Unbalncediet shows among 76.4% of participants .Conclusions and Recommendations : all participant modified their diet,half of the participants had lowenergy intake and some of the participants had underweight .Emphasized the importance for patients to beprovided with nutrition – related knowledge as a part of strategies to avoid nutritional inadeqancies